Kajian Psikolinguistik Pada Proposisi Citra Merek - Anisatul Fauziah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
This study aims to examine or analyze the proposition on the brand image of noodles and meatballs in lumajang based on psycholinguistic review. Research on language proposition on brand image using qualitative research type and designed using case study design. The relationship between the arguments and predictions that emerged in the research data showed varied languages. The contents of the proposition on the brand image of